RANCANG BANGUNSISTEM INKUBATOR PINTARBERBASIS I o T DAN ESP3 2 UNTUK PEMANTAUAN JARAKJAUH KONDISI BAYI SECARA REAL TIME - Galih Bagas Larasanto (2024)
In 2012, the World Health Organization (WHO) reported that approximately 11.1% of the total 135 million infants born worldwide were premature. Indonesia itself is among the top 10 countries with a premature birth rate exceeding 15%. The high prevalence of premature births in Indonesia underscores the importance of facilities for premature infant care, especially incubators, to reduce the mortality rate of premature infants. Critical aspects that need monitoring in an incubator involve heart rate, body temperature, and weight of premature infants, as well as the temperature and humidity of the incubator itself. To address the challenges of periodically monitoring the incubator's temperature, this research employs the Internet of Things. The researcher designed a monitoring system consisting of DHT-22, GY-906, Load Cell, and MAX-30102 sensors, all connected to the ESP32 microcontroller. This system is also supported by the Blynk IoT platform and sends data through the Telegram application. The research results demonstrate the successful real-time monitoring of the incubator from a remote distance using the IoT concept. Warning messages are also successfully sent when the sensor-read parameters deviate from the predefined normal parameters. The accuracy level of the sensors in incubator monitoring is quite high, with the MAX30102 sensor reaching 97.86%, Load Cell 99.91%, GY906 sensor 99.65%, and DHT22 98.3% for temperature and 98.9% for humidity.